2021
DOI: 10.1177/1609406921996855
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 as a Generator of Pending Narratives: Developing an Empirical Tool to Analyze Narrative Practices in Constructing Futures

Abstract: The article describes the basic elements of the pending narrative and develops them into a tool of qualitative analysis by taking examples from Covid-19-related reports, opinions and editorials in the news. The pending narrative is a powerful story form, persuading the responsible actors in public to take action by stirring up compelling passion for a specific goal. It has a cogency that comes from the threat that if we do not act in the right way now, the continuity of life will be jeopardized. Crises are fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, we used sociocultural theory to help us understand, through different social and cultural contexts, how different students experienced the emergency shift to online learning. Master narratives that had been developed in relation to COVID‐19, even as we were writing our paper, were focused on narratives relating to medical and epidemiological facets of the epidemic, such as the plague originating in Asia and the European methods of fighting plague as the only successful way to end the disease (e.g., Törrönen, 2021; Varlık, 2020). We were unable to find published master narratives relating to education.…”
Section: Introductionmentioning
confidence: 99%
“…However, we used sociocultural theory to help us understand, through different social and cultural contexts, how different students experienced the emergency shift to online learning. Master narratives that had been developed in relation to COVID‐19, even as we were writing our paper, were focused on narratives relating to medical and epidemiological facets of the epidemic, such as the plague originating in Asia and the European methods of fighting plague as the only successful way to end the disease (e.g., Törrönen, 2021; Varlık, 2020). We were unable to find published master narratives relating to education.…”
Section: Introductionmentioning
confidence: 99%
“…Several theorists ( Arsenian & Arsenian, 1948 ; Halford & Leonard, 2001 ; Hofstede, 2011 ) suggested that a tough culture - masculine in this case - provides few valued goals and severely restricts access to the pathways through which that goal may be achieved. This type of culture might offer fewer scenarios for the future, or in the words of Törrönen, fewer “pending narratives” ( Törrönen, 2021 ), or strivings, which were found to be associated with life satisfaction ( Emmons, 1986 ). This may be one of the reasons for fewer expectations shared by women in masculine cultures; indeed, the only future expectation associated with masculine societies was for a return to daily activities which were restricted during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic is an example of a disruption that introduced multiple uncertainties and matters of concern to everyday actions. As Covid-19 unsettled our current neoliberal economic, material, political, institutional, and socio-cultural habits and practices, it sent us to build new kinds of actants, relations and assemblages with which we aimed to overcome the difficulties and stabilize new kinds of routines for our everyday lives ( Törrönen, 2021 ).…”
Section: A Social-materials Approachmentioning
confidence: 99%
“…After arriving among us, the Covid-19 virus was soon categorized as a global threat to the continuity of human life, menacing the overall foundations and practices of the current neoliberal economic, political, social and cultural arrangements ( Törrönen, 2021 ). In March and April 2020, diverse kinds of restrictions on social proximity around the world were introduced.…”
Section: Introductionmentioning
confidence: 99%